2023
DOI: 10.1186/s40545-022-00508-x
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension self-care practice and its associated factors in Bale Zone, Southeast Ethiopia: A multi-center cross-sectional study

Abstract: Background Hypertension is a serious threat to public health globally owing to its high prevalence and related complications. It is the main risk factor for cardiovascular disease, kidney disease, eye problems, and death. Self-care practices have been emphasized as a major element in reducing and preventing complications from hypertension. Thus, this study aimed to assess hypertension self-care practices and associated factors in Bale Zone, Southeast Ethiopia. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Several studies have indicated that age is one of the factors influencing self-management behaviors 22 . The study by Tebelu et al 21 demonstrated that the proportion of good self-management practices was 3.77 times higher in younger individuals (i.e., patients under 65 years old) compared to older adults (i.e., patients aged 65 and above). These findings emphasize the importance of considering demographic characteristics such as gender, occupation, economic status, and living status when examining selfmanagement behaviors among hypertensive patients.…”
Section: Factors Related To Hypertension Selfmanagement Behaviorsmentioning
confidence: 99%
“…Several studies have indicated that age is one of the factors influencing self-management behaviors 22 . The study by Tebelu et al 21 demonstrated that the proportion of good self-management practices was 3.77 times higher in younger individuals (i.e., patients under 65 years old) compared to older adults (i.e., patients aged 65 and above). These findings emphasize the importance of considering demographic characteristics such as gender, occupation, economic status, and living status when examining selfmanagement behaviors among hypertensive patients.…”
Section: Factors Related To Hypertension Selfmanagement Behaviorsmentioning
confidence: 99%